The relationship between tooth color, skin and eye color - Teuta Pustina-Krasniqi; Edit Xhajanka; Nexhmije Ajeti; Teuta Bicaj; Linda Dula; Zana Lila (Istanbul University, 2018)
Tooth color is one of the most important factors in dental and facial esthetics. The aim of this study was to determine the tooth color of the upper frontal teeth in subjects and to provide comparisons with different skin and eye colors. Material and methods Tooth color was determined in 255 patients in the intercanine sector of the maxilla using an intraoral spectrophotometer Vita Easyshade® (Vita Zahnfabrik. H Rauter GmbH & Co. KG. Bad Sackingen. Germany). Skin and eye color was determined by visual perception. The shades of the Vita Tooth Guide 3D Master (Vita Zahnfabrik, H Rauter GmbH & Co, KG, Bad Sackingen, Germany) were registered by the spectrophotometer. Pearson's chi-squared test was used to examine the differences between tooth color and skin and eye color. Results The most frequent shade registered in the central incisors was 2M1 (62 subjects, 8.10%); in the lateral incisors, 1.5M1.5 (65 subjects, 8.50%); and in the canines, 2M3 (142 subjects, 18.56%). Pearson's chi-squared test results showed a statistically significant difference in the relations between skin and eye color and central incisor color (p<0.01; p<0.001), lateral incisor color (p<0.001), and canine color (p<0.001; p=0.001). On the other hand, no significant difference was observed in the relation of the lateral incisors and canines with eye color. Conclusion Skin and eye color significantly correlate with tooth color; however, the color of lateral incisors and canines does not correlate significantly with eye color.